Design of a miniaturized wideband disc monopole antenna used in RFID systems - Sufyan Hazzaa Ali; Ahmed Hameed Reja; Yousif Azzawi Hachim (Institute of Advanced Engineering and Science, 2021)
Radio-frequency identification (RFID) is an important wireless technology which utilizes radio frequencies (RFs) for exchanging data between two or more points (tags and readers), that represent an automatic identification (Auto-ID) system. This paper introduces an omnidirectional microstrip antenna operates at 2.45 GHz used for a radio-frequency identification (RFID) technology. The length of the proposed antenna is 36.5 mm and the width is 27 mm. The substrate material which has been used as a base of antenna is FR4 that has dielectric constant value of 4.3 and dielectric thickness value of 1.6 mm. Regarding the resonance frequency, return loss of the proposed antenna design is -34.8 dB. A promising directivity outcome of 2.8 dB has been achieved with omnidirectional radiation pattern as well as an acceptable efficiency of 66%. The proposed antenna design accomplishes a wideband frequency of 1.21 GHz in the frequency range of (2.14 3.35) GHz. The computer simulation technology (CST) microwave studio software has been used for implementing the proposed antenna design. The antenna design fabricatation and its characteristics have been measured using vector network analyzer (type MS4642A). The obtained results of the experimental design achieve a little bit differences as compared with the simulation results